2020
DOI: 10.3892/etm.2020.9558
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents renal cell apoptosis in acute kidney injury in a rat model of dry‑heat environment heatstroke via inhibition of the mitochondrial apoptotic pathway

Abstract: Heatstroke is a life-threatening illness that is characterised by a core body temperature >40°C and central nervous system dysfunction. Acute kidney injury (AKI) is a common complication of heatstroke, and the mitochondrial apoptotic pathway has been demonstrated to be one of the leading causes of tissue damage and cell death in AKI. Curcumin is a phenol that is extracted from turmeric and demonstrates anti-apoptotic properties. To test if curcumin can protect the kidney from injury caused by heat stress, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the current study, HS group revealed an elevation of caspase-3 scores, Meanwhile, the anti-apoptotic marker Bcl-2 scores were significantly lowered. Similarly, caspase-3 level was found to be increased in a rat model of dry heat environment induced heatstroke carried out by Zhao et al (2021). On the contrary, The Dexa-injected group showed a decrease in caspase-3 scores and an increase in Bcl-2 ones, suggesting another putative pathway by which Dexa might attenuate cell death.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the current study, HS group revealed an elevation of caspase-3 scores, Meanwhile, the anti-apoptotic marker Bcl-2 scores were significantly lowered. Similarly, caspase-3 level was found to be increased in a rat model of dry heat environment induced heatstroke carried out by Zhao et al (2021). On the contrary, The Dexa-injected group showed a decrease in caspase-3 scores and an increase in Bcl-2 ones, suggesting another putative pathway by which Dexa might attenuate cell death.…”
Section: Discussionmentioning
confidence: 90%
“…The formalin‐fixed kidney tissue was dehydrated in graded alcohol, cleared with xylene, and embedded in paraffin as blocks. Sections of 4 μm in thickness were sliced, stained with hematoxylin–eosin (H&E) stain, and examined for histopathological changes using Paller's score according to Zhao et al (2021). Briefly, 10 randomly selected fields were analyzed (×400) and 100 cortical tubules were scored.…”
Section: Methodsmentioning
confidence: 99%
“…These factors lead to intestinal ischemia, which induces the generation of intestinal free radicals and intestinal mucosal edema and increases intestinal permeability, all of which promote intestinal disruption and lead to the release of a large number of intestinal toxins into the blood circulation (13,109,(151)(152)(153)(154)(155)(156)(157)(158). Renal failure is a common complication of heatstroke that is mainly manifested as tubular necrotizing acute renal failure and can be caused by massive protein deposition in the renal tubular epithelial cells after hemolysis and rhabdomyolysis (13,21,(158)(159)(160)(161)(162)(163)(164)(165)(166). Liver dysfunction in patients with heatstroke and in animal models is considerably common, with the liver injury mainly occurring in the recovery period of heatstroke (167)(168)(169)(170)(171)(172)(173)(174).…”
Section: Tissue Injury Responsesmentioning
confidence: 99%
“…This was achieved through the activation of antioxidant-related enzymes and the alleviation of physiological disorders [ 56 ]. Meanwhile, Zhao et al [ 57 ] observed that curcumin significantly reduced the concentration of creatinine and blood urea nitrogen in serum, thereby preventing acute kidney injury in heatstroke rats. Apart from the effects on various organs of the body, during heat stress, albino rats exhibited restlessness, hypoactivity, a depressed attitude, and altered behavior.…”
Section: Curcumin In Stress Management Of Terrestrial Animalsmentioning
confidence: 99%